Comparison of the effectiveness of four group therapies in improving the quality of life in menopausal women - Jafary, Forugh; Afzali, Leila (Menopause Review/Przegląd Menopauzalny, 2013)
The aim of the study was to compare the effectiveness of group therapy based on meaning in life, self-efficacy, body image or the combination of the three factors in improving the quality of life in menopausal women. Material and methods : The research sample consisted of 54 menopausal women (45-55 years) selected from women’s associations at cultural centers in Tehran. There were four experimental groups (group therapy based on meaning in life, self-efficacy, body image and a combination of the three factors) and a control group. A quality of life questionnaire (sf-36) was used as a pre-test, post-test and follow-up test (3 months after group therapy) measure in each of the five groups. The group therapy sessions for the experimental groups were held 12 times (for 3 months). Statistical analysis was performed using variance analysis tests, Schefe follow-up tests and covariance analysis. Results: Results of covariance analysis showed a significant increase in quality of life as a result of group therapy based on meaning in life (p < 0.05), group therapy based on self-efficacy (p < 0.05) and group therapy based on the combination of three factors (p < 0.01). Group therapy based on body image alone resulted in no significant changes in quality of life. Follow-up test results after the three-month period showed continuity of the results. Conclusions: Group therapy based on a combination of meaning in life, self-efficacy and body image offers a higher and more durable increase in quality of life.